Kinetika Oksidasi Protein Ikan Kakap (Lutjanus sp) Selama Penyimpanan - Rahim Husain; Suparmo Suparmo; Eni Harmayani; Chusnul Hidayat (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
Fish protein is oxidased easily during storage. The oxidation reaction rate can be approached through the order to zero or first order. The objective of this research was to study the oxidation rate during storage by determining the amount of activation energy (Ea) and constant change (k). The results showed that the increased of temperature storage from 0 °C to 40oC can increased the k value from 0.0617 to 0.311. The carbonyl content of red snapper protein isolate can be increased to higher level as storage temperature increase to 40 °C with higher level increase at higher temperature. The activation energy of oxidation reactions that cause oxidation of the protein is 42.015 Kj/mol.K to zero order. Kinetics increase in protein carbonyls: the higher the temperature storage protein isolate red snapper (Lutjanus sp), the greater the value of a constant (k) is obtained. Kinetics studies show that an increase in the rate of reaction of oxidative damage fish protein (Lutjanus sp) during storage by following zero order reactions. ABSTRAKProtein ikan mudah rusak akibat oksidasi selama penyimpanan. Kecepatan reaksi oksidasi dapat didekati melalui orde ke nol maupun orde pertama. Penelitian ini bertujuan untuk mempelajari oksidasi selama penyimpanan dengan menentukan besaran energi aktivasi (Ea) dan konstanta perubahan (k). Hasil menunjukkan bahwa nilai k meningkat dari 0,0617 menjadi 0,311 dengan peningkatan suhu dari 0 °C ke 40 °C. Energi aktivasi reaksi oksidasi yang menyebabkan terjadinya oksidasi protein adalah 42,015 Kj/mol.K untuk orde nol. Kinetika peningkatan protein karbonil: semakin tinggi suhu penyimpanan protein ikan kakap (Lutjanus sp) semakin besar nilai konstanta (k) yang diperoleh. Studi kinetika juga memperlihatkan bahwa peningkatan laju reaksi kerusakan oksidasi protein ikan kakap (Lutjanus sp) selama penyimpanan mengikuti reaksi orde ke nol atau reaksi berjalan lambat.